Parametric control for multiscroll generation: Electronic implementation and equilibrium analysis. (November 2020) - Echenausía-Monroy, J.L.; García-López, J.H.; Jaimes-Reátegui, R.; Huerta-Cuéllar, G.
Abstract: This paper presents a novel electronic implementation based on a simple methodology to control the number of scrolls generated, by means of operational amplifiers and a single control parameter. Through the use of a Saturated Non Linear Function (SNLF) for the generation of a 9-scroll attractor, the number of scrolls is modified through a single parameter. In addition, the implemented system is also capable of generating a family of bistable behaviors. The phenomenon for the scroll generation, induced by a control parameter, is explained through the system equilibrium points. This methodology can be extended to system's with higher number of scrolls, or systems with larger basins of attraction. The results shown have high potential application in secure communication systems, mobile surveillance devices, pseudo-random number generators and complex networks, among others.